First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Ten-year exposure to household air pollution is associated with obstructive sleep apnoea - Yaoyao Qian; Garun S. Hamilton; Chamara V. Senaratna; Caroline J. Lodge; Michael J. Abramson; Xin Dai; Dinh S. Bui; Anurika P. De Silva; Paul S. Thomas; Bircan Erbas; Eugene H. Walters; Jennifer L. Perret; et al. (Environmental Research, 2025)

Deep learning approach to detect and visualize sexual dimorphism in monomorphic species - Nicolas J. Silva; André C. Ferreira; Liliana R. Silva; Samuel Perret; Sonia Tieo; Julien P. Renoult; Rita Covas; Claire Doutrelant (Animal Behaviour, 2025)

Continental Patterns of Phenotypic Variation Along Replicated Urban Gradients: A Mega‐Analysis - M. J. Thompson; J. G. A. Martin; C. Biard; J. Bleu; C. J. Branston; P. Capilla‐Lasheras; N. J. Dingemanse; D. M. Dominoni; M. Eens; T. Eeva; K. L. Evans; C. Isaksson; et al. (Ecology Letters, 2025)
Individual variation among and within natural populations can have eco‐evolutionary implications by, for example, affecting species interactions or evolutionary potential. Urban systems present a unique opportunity to evaluate how environmental change shapes variation since urban phenotypic differentiation is widely documented on contemporary timescales. We introduce and test three hypotheses to determine how urbanisation affects phenotypic variation at different population levels. Combining 21 long‐term datasets in a mega‐analysis approach, we synthesise how urbanisation impacts variation in tarsus length and lay date among and within subpopulations of great and blue tits ( Parus major , Cyanistes caeruleus ) at a continental scale. Our synthesis reveals that urbanisation is associated with increased phenotypic variation within subpopulations by 11% on average, and by as much as 25% across the species and traits examined. We also find some evidence (for tarsus length in great tits) that urbanisation increases differentiation between subpopulations. We did not, however, find that urbanisation increases differences between subpopulations in their within‐subpopulation variation. Our synthesis provides novel insights into how urban contexts impact individual diversity at different spatial scales and we highlight future directions that could establish the genetic and environmental effects that underlie these continental patterns of urban phenotypic variation.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Where are we now with European forest multi-taxon biodiversity and where can we head to? - Sabina Burrascano; Francesco Chianucci; Giovanni Trentanovi; Sebastian Kepfer-Rojas; Tommaso Sitzia; Flóra Tinya; Inken Doerfler; Yoan Paillet; Thomas Andrew Nagel; Bozena Mitic; Lourdes Morillas; Silvana Munzi; et al. (Biological Conservation, 2023)

Resistance of the oyster pathogen Vibrio tasmaniensis LGP32 against grazing by Vannella sp. marine amoeba involves Vsm and CopA virulence factors - Etienne Robino; Aurore C. Poirier; Hajar Amraoui; Sandra Le Bissonnais; Angélique Perret; Carmen Lopez‐Joven; Jean‐Christophe Auguet; Tristan P. Rubio; Chantal Cazevieille; Jean‐Luc Rolland; Yann Héchard; Delphine Destoumieux‐Garzón; et al. (Environmental Microbiology, 2020)
Summary Vibrios are ubiquitous in marine environments and opportunistically colonize a broad range of hosts. Strains of Vibrio tasmaniensis present in oyster farms can thrive in oysters during juvenile mortality events and behave as facultative intracellular pathogen of oyster haemocytes. Herein, we wondered whether V . tasmaniensis LGP32 resistance to phagocytosis is specific to oyster immune cells or contributes to resistance to other phagocytes, like marine amoebae. To address this question, we developed an integrative study, from the first description of amoeba diversity in oyster farms to the characterization of LGP32 interactions with amoebae. An isolate of the Vannella genus, Vannella sp. AP1411, which was collected from oyster farms, is ubiquitous, and belongs to one clade of Vannella that could be found associated with Vibrionaceae . LGP32 was shown to be resistant to grazing by Vannella sp. AP1411 and this phenotype depends on some previously identified virulence factors: secreted metalloprotease Vsm and copper efflux p‐ATPase CopA, which act at different steps during amoeba–vibrio interactions, whereas some other virulence factors were not involved. Altogether, our work indicates that some virulence factors can be involved in multi‐host interactions of V . tasmaniensis ranging from protozoans to metazoans, potentially favouring their opportunistic behaviour.

Shape plasticity in response to water velocity in the freshwater blenny Salaria fluviatilis - M. Laporte; J. Claude; P. Berrebi; P. Perret; P. Magnan (Journal of Fish Biology, 2016)
A non‐random association between an environmental factor and a given trait could be explained by directional selection (genetic determinism) and by phenotypic plasticity (environmental determinism). A previous study showed a significant relationship between morphology and water velocity in Salaria fluviatilis that conformed to functional expectations. The objective of this study was to test whether this relationship could be explained by phenotypic plasticity. Salaria fluviatilis from a Corsican stream were placed in four experimental channels with different water velocities (0, 10, 20 and 30 cm s −1 ) to test whether there was a morphological response associated with this environmental factor. After 28 days, fish shape changed in response to water velocity without any significant growth. Fish in higher water velocities exhibited a more slender body shape and longer anal and caudal fins. These results indicate a high degree of morphological plasticity in riverine populations of S. fluviatilis and suggest that the previous relationship between morphology and water velocity observed in the field may largely be due to an environmental determinism.

Morphological variation in the freshwater blenny Salaria fluviatilis from Corsican rivers: adaptive divergence, phenotypic plasticity or both? - P. Magnan; R. Proulx; P. Berrebi; J. Blondel; P. Perret; B. Roché (Journal of Fish Biology, 2014)
The first goal of this study was to determine whether morphological variation in the freshwater blenny Salaria fluviatilis results in spatially structured populations distributed around Corsica, France, which would suggest genetically differentiated populations through reproductive isolation by distance. The second goal was to determine whether some morphological traits are related to water velocity, one of the most contrasting habitat characteristics in these rivers, which would suggest an adaptation to local conditions. The results showed that the morphology of S. fluviatilis differed among the three main geographic areas studied in Corsica and that geographically distant populations of S. fluviatilis were less similar morphologically and genetically than close ones. The results also indicated that the morphological differences among populations conformed to functional expectations. Overall, the results suggest that the morphological variation of S. fluviatilis from Corsican rivers is an adaptive response to water velocity and that these populations are in a process of reproductive isolation by distance.

Fishing Farmers or Farming Fishers? Fishing Typology of Inland Small-Scale Fishing Households and Fisheries Management in Singkarak Lake, West Sumatra, Indonesia - Yuerlita; Sylvain Roger Perret; Ganesh P. Shivakoti (Environmental Management, 2013)

Spatial assessment of climate change effects on crop suitability for major plantation crops in Sri Lanka - P. M. S. Jayathilaka; Peeyush Soni; Sylvain R. Perret; H. P. W. Jayasuriya; Vilas M. Salokhe (Regional Environmental Change, 2012)

Construction of an oilseed rape (Brassica napus L.) genetic map with SSR markers - J. Piquemal; E. Cinquin; F. Couton; C. Rondeau; E. Seignoret; I. doucet; D. Perret; M.-J. Villeger; P. Vincourt; P. Blanchard (Theoretical and Applied Genetics, 2005)

Transformation of oat and inheritance of bar gene expression - B. Kuai; S. Perret; S. M. Wan; S. J. Dalton; A. J. E. Bettany; P. Morris (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Mapping quantitative trait loci controlling silking date in a diallel cross among four lines of maize - A. Rebaï; P. Blanchard; D. Perret; P. Vincourt (Theoretical and Applied Genetics, 1997)

Editorial - P. Perret (Aquatic Sciences, 1985)

Buchbesprechungen - Peter Perret; P. Bossard; B. M. Novak (Aquatic Sciences, 1974)